Efektivitas Media Audio Visual Dalam Meningkatkan Pengetahuan Tentang Seribu Hari Pertama Kehidupan Remaja Putri - Sunaeni Sunaeni; Al Inayah M. Abduh; Mariana Isir (Universitas Malahayati Lampung, 2022)
ABSTRACT Understanding nutrition in the first thousand days of human life needs to be promoted in preventing stunting. Adolescent girls have a key role in maintaining health during pregnancy, of which 28.72% of women in West Papua aged 15-19 years (SMP-SMA) are pregnant for the first time. Audio-visual media can be used as an alternative in disseminating information on stunting prevention during the